Sustained-release Oral Hydromorphone for the Treatment of Opioid Use Disorder. Issue 4 (July 2020) - Braithwaite, Vivian; Fairgrieve, Christopher; Nolan, Seonaid
Abstract : Objectives: In 2017, almost 50, 000 Americans and over 4000 Canadians died from an opioid overdose. Accordingly, an urgent need exists to improve access to evidence-based treatment for opioid addiction, and also to develop and evaluate alternative treatment options for opioid use disorder (OUD). We present a case of a patient with OUD who was successfully switched and managed on oral hydromorphone after development of a prolonged QTc interval on methadone. Case: A 51-year-old man with longstanding polysubstance use presented to an urban hospital in Vancouver, Canada, for management of alcohol intoxication and hyponatremia. At the time of admission, the patient was stable on 100 mg of methadone daily, but was found to have a persistently elevated QTc (>550 milliseconds), putting him at increased risk for Torsades de Pointes. In an effort to find an alternative opioid agonist therapy for maintenance, a trial of slow-release oral morphine was attempted, but discontinued due to the development of myoclonus. Once-daily sustained-release oral hydromorphone was then started, which was found to manage cravings well without notable side effects. Discussion: The case presented offers promise for the use of once-daily sustained-release oral hydromorphone as a viable treatment option for patients with OUD for whom first-line therapies are not suitable or tolerated. This case report is the first to our knowledge to demonstrate the successful use of oral hydromorphone for treatment of opioid use disorder.